(3GdeMOK GdaGUd Hjf GdQGhi hGdhGYis - (3Hf NdGO , GdMSf Hf YHO GdQMef Hf NdGO GdQGegQeRj, CHh eMeO,J (B360 (3g` s
(3ChdgG (B:s
(3jHOC HHGH aVd GdfGbd dSfI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3jfJgi CKfGA HGH Gdbhd ai GdJYGdi hGdJfRd ajg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydg SeGY Ydi GdMGaX GdSdai SfI (B525(3g` hNW GdMGaX HPdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B235s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1612s
Keywords: (3GdMOjK h GdeUWdMs